Practical training report at Petra Energy Miri / Muhamad Afzal Jahangir - Jahangir, Muhamad Afzal (University Technology MARA Sarawak, 2018)
Petra Energy Berhad (Petra Energy) is an organization that has been founded in early 1980’s and is headquartered in Petaling Jaya, Malaysia. Petra Energy spearheads a consortium of subsidiary companies (together referred as the Group), provides a comprehensive range of integrated brown field services for the upstream oil & gas industry and specialist products and services for the petrochemical industry. The Group is also involved in development and production activities of small field cluster. In the corporate structure, the Petra Energy consists of 3 segment which are the service segment, the marine asset segment and the development and production segment. As for the each segment those segments have various kinds of units which help to support the Petra Energy group operation. For the service segment, there are four (4) units under the segment.